PENGARUH JUMLAH PINTU MAKAN TERHADAP PRODUKSI TELUR BURUNG PUYUH - Armen, Armen; Novriyanti, Ernie (Sainstek : Jurnal Sains dan Teknologi, 2013)
This study aims to determine the effect of the number of doors eating quail egg production. The study population quail - coturnic Coturnix japonica strains 500 hatching tails of the results using the incubator. All members of the population have the same criteria include age, weight, health , and gender. The design used in this study is completely randomized design with 5 treatments and 5 replications. Treatment (A) 20 tail with 20 % quail feed doors, treatment (B) 20 tail quail with 40 % door dining, treatment (C) 20 tail quail with 60 % door dining , treatment (D) 20 tail quail with 80% of doors eating, treatment ( E ) 20 tail quail with 100 % door to eat. Further test used is Advanced Test Significant Difference at 5% level. The results showed that the number of doors eating very influential on the production of quail egg. Egg production was highest on the cage doors have eaten as much as the number of quail. Lowest egg production contained in the enclosure that has a door to eat as much as 20 % of the number of quail with the effect of each treatment is very real.Key words: total door eat , quail egg production